ANALISIS TERHADAP EKSEKUSI DALAM PUTUSAN SERTA MERTA (UITVOERBAAR BIJ VOORRAAD) - Harly Stanly Muaja; Roy Ronny Lembong; Prisilia F. Worung (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study aims to determine the requirements for the implementation of a decision that can be implemented in advance/immediately (uitvoerbaar bij voorraad) and to find out about the execution of a decision that can be implemented in advance/immediately not accepted by the losing party. By using the normative research method, the following conclusions can be drawn: 1. The requirements in the decision immediately authorize the District Court to determine in the final decision (as stated in the HIR or RBg.) by paying attention to the Circular of the Supreme Court according to which the final decision can be implemented in advance (immediately) even though there is a denial or appeal. The requirements through Decision Number 04/Pdt.G/2023/PN.Mdo regarding the granting of the immediate decision are the implementation of the execution first against the object of the dispute even though there are legal remedies, ordering or punishing the defendant to vacate the object of the dispute if the defendant does not voluntarily leave the object of the land dispute. The emergence of legal certainty regarding the rights of ownership and control over the disputed land and the creation of justice for the Plaintiff. That this is in accordance with the purpose of the law, namely that the law must be able to create justice, certainty and benefits for all people without exception. 2. Execution of the decision immediately if it is not accepted by the losing party, then through the applicant for execution if the decision is not implemented, it will be carried out by coercive measures by legal force. The coercive measures are carried out based on a letter of determination of recovery issued by the Head of the District Court.